Compromises and Customs: Strategic Practices in Bugis Sinjai Traditional Marriages - Muslim, Abu; Idham, Idham; Mujizatullah, Mujizatullah; Marannu, Baso; Yuwono, Dandung Budi (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
In the Bugis community of Sinjai, customary marriage practices embody sacred unity and family honor, often imposing strict conditions that can challenge individuals striving to achieve their marriage goals. One major obstacle is the high cost of marriage, which is further complicated by the influences of modernity and freer social interactions that have shifted the purpose of marriage away from its original religious intentions. As a result, marrying according to Bugis customs entails significant financial burdens, leading some individuals to adopt compromises and strategic tactics as alternative solutions. This research explores how such compromises and strategies are employed in Bugis marriages within Sinjai Regency, South Sulawesi. Using a qualitative case study approach, data were collected through observation, interviews, and documentation. The analysis draws on perspectives from Islamic jurisprudence, Bugis cultural traditions, and ethics. The research identifies two primary categories of strategies: first, compromises or strategies used to overcome obstacles in proceeding with marriage; second, strategies driven by specific goals or interests underlying the decision to marry. Five distinct case types are examined: political marriage, elopement, polygamy strategies, passampo siri (a form of symbolic compensation), and resource pooling (dui menre). Findings suggest that while these compromises and strategies may have limitations and potential negative consequences if misapplied, they also serve as practical adaptations to the rigid demands of Bugis customary marriage. The study underscores the importance of applying social ethics to frame marriage beyond legalistic terms, recognizing it as a genuine worldly and spiritual union that prioritizes public welfare and prevents harm